THE ROLE OF A TEACHER IN COMMUNICATIVE TECHNIQUES - Karshi SU; Turayeva G. (Western European Studies, 2024)
The article discusses the role of a teacher in creating authentic practice activities that as similar to real-life. Teachers can influence learners` motivation is by making the classroom a supportive environment. Hence, the teacher will actually assume roles to model the language for the learners, or act as someone for the learners to communicate with.
Keywords: teacher role; motivate; stimulate